2008
DOI: 10.1002/ijc.23815
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the regions of the HPV 5 E6 protein involved in Bak degradation and inhibition of apoptosis

Abstract: UVB induced DNA damage is the major aetiological agent in NMSC development, but mounting evidence suggests a role for human papillomaviruses (HPV) from genus beta, including HPV 5 and HPV 8, in the development of NMSC on sun exposed body sites. We have previously shown that UVB activates Bak, an apoptogenic mitochondrial factor that, following an apoptotic stimulus, undergoes a conformational change that leads to pore formation in the mitochondrial membrane that releases apoptotic factors. The HPV E6 protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
0
27
1
2
Order By: Relevance
“…HPV16 E6 was shown to interact in vitro with the karyopherins ␣2, ␤1, and ␤2 (37), suggesting that E6 is actively imported in the nucleus. Our subcellular localization of the 29 HPV E6 proteins used in this study, as fusions with YFP, showed that the E6 proteins from HPV types 11,16,18,26,30,31,33,34,35,39,42,45,51,52,53,56,58,59,66,68,69,70,73,82,83, and 97 accumulate predominantly in the nucleus after transfection (Fig. 5).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…HPV16 E6 was shown to interact in vitro with the karyopherins ␣2, ␤1, and ␤2 (37), suggesting that E6 is actively imported in the nucleus. Our subcellular localization of the 29 HPV E6 proteins used in this study, as fusions with YFP, showed that the E6 proteins from HPV types 11,16,18,26,30,31,33,34,35,39,42,45,51,52,53,56,58,59,66,68,69,70,73,82,83, and 97 accumulate predominantly in the nucleus after transfection (Fig. 5).…”
Section: Discussionmentioning
confidence: 67%
“…Accordingly, transgenic mice expressing E6 in the skin develop malignant skin tumors, whereas E7 expression induces primarily benign hyperplasia (25,54,55). In addition to its ability to degrade p53, E6 was also shown to target several other proteins, among which is the multidomain proapoptotic protein Bak (14,30,51,64,65,69). This activity is thought to be important to prevent apoptosis of infected cells and to favor the transformation process.…”
mentioning
confidence: 99%
“…E6 proteins encoded by b-HPVs do not in general share this function; however, a recent report suggested that the HPV49 E6 protein is able to target p53 for degradation to some degree (Cornet et al, 2012), but whether this is dependent on the p53 isoform (Storey et al, 1998), as noted previously for specific mutants of HPV5 E6 (Simmonds & Storey, 2008), remains to be determined. Nevertheless, transgenic mice expressing the HPV8 E6 protein mimic expression of the complete early region of the HPV8 genome, in that E6 expression leads to papilloma formation, which can progress spontaneously to SCC (Marcuzzi et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…2b). Whilst other mutations generated across the HPV5 E6 protein do not affect its stability (Simmonds & Storey, 2008), we cannot rule out at this time whether or not these mutations at the C terminus alter E6 structure or stability. Empty lanes were left between each sample on the gel to limit sample cross-contamination (indicated by the background staining observed).…”
mentioning
confidence: 94%
“…the intrinsic pathway, which triggers sensing apoptotic signals that arise within the cell (DNA damage, oxidative stress) [54]. The lr/hrE6 oncoproteins block intrinsic apoptotic signaling interacting with Bak, inducing its proteasomal-dependent degradation [55], or using a mechanism depending or not on E6AP and E3 ubiquitin ligases [56].…”
Section: E6 Hpvmentioning
confidence: 99%